(untitled) (Informatica, 2016)
The Enterprise edition of the Java platform has been endorsed by both small and large enterprises, as it enables the development of large-scale, reliable, and secure software solutions. In the world of agent development, on the other hand, AgentSpeak, and its practical interpreter Jason, represent one of the most popular tools for writing complex, reasoning agents. This paper presents a framework that integrates the two approaches to distributed software development, and supports a seamless deployment of Jason agents in enterprise environments. The proposed framework o ers many technical advantages, including automated agent load-balancing and fault-tolerance. The end-goal of this research, however, is to try and bridge the gap between the agent technology and modern enterprise applications.